2019
DOI: 10.1186/s40560-019-0391-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a rapid molecular blood test on the use of antibiotics for nosocomial sepsis: a randomized clinical trial

Abstract: Background Appropriate use of antimicrobials is essential to improve outcomes in sepsis. The aim of this study was to determine whether the use of a rapid molecular blood test—Septi Fast (SF) reduces the antibiotic consumption through early de-escalation in patients with nosocomial sepsis compared with conventional blood cultures (BCs). Methods This was a prospective, randomized, superiority, controlled trial conducted at Sao Paulo Heart Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…During this period, we observed that the microbiology laboratory, despite having the MALDI-TOF, waited the 24-h incubation period for bacteria identification. Therefore, after identifying the species directly from bottles of positive blood culture, we started to perform this technique during the intervention period, in addition to a rapid communication to the prescribing physician and the detection of resistance genes [ 11 , 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this period, we observed that the microbiology laboratory, despite having the MALDI-TOF, waited the 24-h incubation period for bacteria identification. Therefore, after identifying the species directly from bottles of positive blood culture, we started to perform this technique during the intervention period, in addition to a rapid communication to the prescribing physician and the detection of resistance genes [ 11 , 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results from rapid molecular tests performed on blood cultures flagged positive during the intervention period showed a high prevalence of microbiological isolates producers of ESBL (68.6%), oxacilinases (41.2%), and KPC (27.4%). Knowledge of the resistance mechanism before the susceptibility test is a very useful point-of-care and highly recommended tool that certainly contributes to the de-escalation and adjustment of the antimicrobial regimen [ 3 , 18 , 19 , 25 ]. It remains to be seen what the long-term impact will be of reducing bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, use of LightCycler SeptiFast (Roche Diagnostics, Switzerland) has led to a significant decrease in time to de-escalation, and reduction in median antibiotic consumption compared to BC-based approach [12 ▪▪ ]. However, no impact on in-hospital mortality was demonstrated with the use of the assay [12 ▪▪ ,15].…”
Section: What Is New In the Diagnosis Of Gram-negative Bloodstream In...mentioning
confidence: 99%
“…Nucleic acid amplification tests (NAAT) identify pathogens in about 6 h directly after the blood was drawn. Whenever tested in the clinical setting, its performance remains, however, insufficient for prime clinical use [16 ▪ ,17–19]. The T2 magnetic resonance (T2MR) is a newer fully automated method that detects a range of pathogens directly on whole blood.…”
Section: Advances In Diagnostics Relevant To Gram-negative Bacteriamentioning
confidence: 99%